The effect of climate disclosure on stock market performance: Evidence from Norway. (2nd November 2022) - Antoniuk, Yevheniia
Abstract: Increased concerns about climate change and its economic impact emphasize the necessity of sustainable investment and have become a demanded research topic. Via voluntary carbon and climate‐related disclosure, companies indicate their exposure to climate change risks and how they counteract them. Investors seeking to reduce the climate risk of their portfolios can utilize this information. Using the 2010–2020 Carbon Disclosure Project scoring for companies in Norway, I formed portfolios of stocks with high, low, and no scores. These portfolios represent lower, higher, and unknown climate risks, respectively. The results suggest that a value‐weighted portfolio of firms with high scores generates an extra 1.3% annualized return over the market. This portfolio steadily outperformed the market in recent years based on the information and Sortino ratios. However, after controlling for recognized risk factors, the high‐score portfolio has no abnormal return unless energy stocks are excluded. In contrast, low‐ and no‐score portfolios were penalized for bearing higher climate risk so that there is a significant climate alpha after 2016. This research highlights that a climate‐aligned investment strategy is profitable while offering lower climate change risk exposure.